Conversion of Carbonyl Compounds to Olefins via Enolate Intermediate. Issue 8 (13th June 2019) - Cao, Zhi‐Chao; Xu, Pei‐Lin; Luo, Qin‐Yu; Li, Xiao‐Lei; Yu, Da‐Gang; Fang, Huayi; Shi, Zhang‐Jie
Summary of main observation and conclusion: A general and efficient protocol to synthesize substituted olefins from carbonyl compounds via nickel catalyzed C—O activation of enolates was developed. Besides ketones, aldehydes were also suitable substrates for the presented catalytic system to produce di‐ or tri‐ substituted olefins. It is worth noting that this approach exhibited good tolerance to highly reactive tertiary alcohols, which could not survive in other reported routes for converting carbonyl compounds to olefins. This method also showed good regio‐ and stereo‐selectivity for olefin products. Preliminary mechanistic studies indicated that the reaction was accomplished through nickel catalyzed C—O activation of enolates, thus offering helpful contribution to current enol chemistry. Abstract :